2020
DOI: 10.3390/ijms21093050
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Triclosan in Porcine Oocyte Leads to Superoxide Production and Mitochondrial-Mediated Apoptosis during In Vitro Maturation

Abstract: While triclosan (TCS) exerts detrimental effects on female reproduction, the effect of TCS-derived toxins on porcine oocytes during in vitro maturation (IVM) is unclear. This study investigated the effects of TCS on mitochondrion-derived reactive oxygen species (ROS) production and apoptosis pathways during porcine oocyte maturation. Porcine oocytes were treated with TCS (1, 10, and 100 μM) and triphenylphosphonium chloride (Mito-TEMPO; 0.1 μM), and matured cumulus oocyte complexes (COCs) were stained with orc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…This confirms previous studies that showed activation of caspase-3 and procaspase-9 in HL-60, SGC-7901, SKOV3, Hela, and B16F1 cells post-juglone treatment [ 2 , 3 , 5 , 47 ]. It also corroborates our above-mentioned records regarding juglone-induced damage in bovine oocytes as well as other studies documenting the induction of cellular apoptosis and reduction of oocyte quality during meiotic progression following the successive accumulation of ROS [ 32 , 39 , 40 ]. Collectively, these results indicated that juglone induces the accumulation of ROS, which in turn can reduce oocyte maturation and induce apoptosis, which can eventually impair the embryo development.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This confirms previous studies that showed activation of caspase-3 and procaspase-9 in HL-60, SGC-7901, SKOV3, Hela, and B16F1 cells post-juglone treatment [ 2 , 3 , 5 , 47 ]. It also corroborates our above-mentioned records regarding juglone-induced damage in bovine oocytes as well as other studies documenting the induction of cellular apoptosis and reduction of oocyte quality during meiotic progression following the successive accumulation of ROS [ 32 , 39 , 40 ]. Collectively, these results indicated that juglone induces the accumulation of ROS, which in turn can reduce oocyte maturation and induce apoptosis, which can eventually impair the embryo development.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, the degree of cumulus expansion correlates with the competence of in vitro oocyte maturation that can eventually predict the developmental competence of embryos [ 31 ]. Similar to our observations, previous studies on porcine COCs showed a significant reduction in cumulus expansion and/or downregulation of HAS2, TNFAIP6, and PTX3 following treatment with juglone and the pro-oxidant molecules atrazine and triclosan [ 25 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to previous study, reduction of superoxidederived oxidative stress by Mito-TEMPO improved oocyte maturation rate and developmental competence in porcine and bovine embryos (Yang et al, 2018;Park et al, 2020;Yousefian et al, 2021). Moreover, freezing medium with Mito-TEMPO supplementation assisted conservation of post-thawed sperm quality and survival competence in human (Lu et al, 2018;Masoudi et al, 2021).…”
mentioning
confidence: 88%
“…TCS has structural similarities to several thyroid hormones and has been shown to have dose-dependent effects on thyroid hormone production in animal studies [149]. Kim et al [150] and Park et al [151] both showed that perinatal TCS exposure caused porcine mitochondrial disruption and oxidative stress. Tran et al [152] demonstrated that perinatal TCS exposure induced neurodevelopment disorders in mice, leading to significant social, cognitive and learning defects in offspring mice.…”
Section: Fate and Impacts Of Triclosan And Triclosan-related Compoundmentioning
confidence: 99%